Citizen endorsement of contested peace settlements: public opinion in post-Dayton Bosnia. Issue 2 (17th February 2021) - Morgan-Jones, Edward; Stefanovic, Djordje; Loizides, Neophytos
ABSTRACT: This article asks what shapes public support for comprehensive peace agreements that aim to end violent conflict in deeply divided societies. Although public perceptions are critical for the success of territorial settlements, little scholarly attention has focused on citizen attitudes towards peace in the post-implementation phase. We develop and empirically test a theory of citizen support for peace agreements that relates power-sharing institutions to broader citizens' security considerations and integrates into this theory the roles of international peacekeeping, ascriptive minority/majority identities and exposure to alternative governance structures (i.e. federal, consociational and centripetalist). We argue that the degree to which a peace treaty provides credible security to citizens determines public support for power-sharing. We test this argument in a least likely case Bosnia Herzegovina. Using data from a 2013 representative survey with 1007 respondents, we examine the determinants of popular support for the Dayton Peace Accords. Our findings suggest that in each of the three main ethnic groups of Bosnia, more people would have voted for Dayton than against it and highlight the mechanisms through which individual and ethnic group security concerns shape support for the country's post-conflict institutions.